Diversity of Indigenous Woody Species in Small Holder Farm Lands: Comparison across Different Agroecology and Land Use Types in Chilga and Dabat District, Northern Ethiopia - Abate, Dagm Fikir; Tebikew, Mekuannint; Gebremariam, Yohannis (International Journal of Scientific Research and Management (IJSRM), 2018)
Ethiopia is known for its massive expansion of plantations and woodlots, that are mainly of monocultures of the exotic tree species, Eucalyptus, which has still remained the pre-dominant tree components of plantations as well as farming systems in different parts of Ethiopian highlands, including the highlands in North Gondar. However, the status of indigenous/native tree species in these areas has become very limited, and is considered at risk. The current study was conducted in Chiliga and Dabat districts of North Gondar zone; it assessed (i) indigenous woody species diversity of farmlands in different agro-ecologies and farm land use categories, (ii) management and conservation practices carried out by farmers, and (iii) major constraints for enhancing on-farm integration of indigenous woody species. Primary data was obtained using such methods as, formal household survey, group discussion, observation and woody species inventory in two villages selected randomly from highland and mid highland for Dabat, and mid land and lowland for Chiliga district. A complete census of all woody individuals was conducted on all plots/parcels of 80 households. A total of 35 species were encountered in the farm lands of the studied area. Six of the total species was exotic, and constitute about 85% of the total abundance. The number of woody species per household increased with decreased agroecological gradient, and the largest value of stem number was found at the highland, followed by at mid highland, whereas least stem number was found in the lowland site. Likewise, the study found that homegardens host more diverse indigenous species than other land use types. Even though farm lands in the study areas were home to different indigenous woody species higher in number than exotic species, it was possible to confirm the already reported evidence that revealed exotic species have been remaining the pre-dominant tree components of the agricultural landscapes in different parts of Ethiopian highlands. However, the fact that remnant native tree individuals are currently growing with in the agricultural landscapes is an indication of the opportunity for integrating and managing native tree species through Agroforestry systems. The study concludes that there is a considerable possibilities of native and indigenous species to exist as an integral component of agricultural land use systems in Northern highlands where Eucalyptus expansion has remained the main focus of research and extension efforts.